Alex Delaware : The Ghost Orchid - Book 39 - Kellerman, Jonathan (New York : Ballantine Books, 2023)
"Psychologist Alex Delaware and Detective Milo Sturgis are faced with their most perplexing case yet when a double homicide investigation leads them to stolen identities and long-buried secrets worth killing for in this riveting thriller from the #1 New York Times bestselling author"--
Keywords: Delaware, Alex -- (Fictitious character) -- Fiction; Detective and mystery fiction; Novels; Thrillers (Fiction)